PERANAN KEPUASAN PELANGGAN SEBAGAI PEMEDIASI PADA PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN - Suhadi Jaka Sugihantara, Rahayu Triastity & Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This study aims to analyze the effect of product quality on customer satisfaction;The effect of product quality on customer loyalty; The effect of customer satisfaction oncustomer loyalty; And the effect of product quality mediated by customer satisfaction.The type of research used is survey research on customer Srabi NotosumanNy.Handayani Solo with a sample of 100 respondents. Sampling technique was done byNonprobabiliti Sampling with purposive sampling technique. Data analysis usingclassical assumption test, path analysis, F test, and test of coefficient of determination.The result of product quality has a significant effect on customer satisfaction, productquality has a significant effect on customer loyalty, customer satisfaction has nosignificant effect on customer loyalty, and customer satisfaction mediates the effect ofproduct quality on customer loyalty.Keywords: customer satisfaction, product quality, customer loyalty